STRATEGI ACTIVE LEARNING DALAM MENINGKATKAN PARTISIPASI SISWA DI SD NEGERI 116 PANYABUNGAN - Kholijar; Mhd Asy'ari; Ali Yusron (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of active learning strategies in improving students’ participation in Islamic Religious Education learning at SD Negeri 116 Panyabungan. This research employed a qualitative approach with a field research design. The research subjects consisted of Islamic Religious Education teachers and elementary school students. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of active learning strategies in Islamic Religious Education learning is carried out through several activities such as group discussions, interactive question-and-answer sessions, collaborative assignments, and experience-based learning activities. The implementation of these strategies was able to increase students’ participation in the learning process, as reflected in students’ involvement in asking questions, answering questions, expressing opinions, and participating in group activities. This study demonstrates that active learning strategies play an important role in creating Islamic Religious Education learning that is more active, participatory, and student-centered.